Catalyst and solvent-free alkylation of quinoline N-oxides with olefins: A direct access to quinoline-substituted α-hydroxy carboxylic derivatives. Issue 9 (5th February 2016) - Kumar, Rakesh; Kumar, Inder; Sharma, Ritika; Sharma, Upendra
Abstract : A catalyst/solvent-free, one-pot and operationally simple method for the synthesis of quinoline-substituted α-hydroxy carboxylic derivatives by the hydroxyheteroarylation of olefins with quinoline N -oxides is reported. Abstract : A catalyst/solvent-free, one-pot and operationally simple method for the synthesis of quinoline-substituted α-hydroxy carboxylic derivatives by the hydroxyheteroarylation of olefins with quinoline N -oxides is reported. The reaction features a high atom-economy, mild and reagent/solvent-free conditions, broad substrate scope and good selectivity with high yields. A preliminary mechanistic study to shed light into the reaction pathway was also carried out.